2021
DOI: 10.3389/fonc.2021.631021
|View full text |Cite
|
Sign up to set email alerts
|

High-Throughput and Automated Acoustic Trapping of Extracellular Vesicles to Identify microRNAs With Diagnostic Potential for Prostate Cancer

Abstract: Molecular profiling of extracellular vesicles (EVs) offers novel opportunities for diagnostic applications, but the current major obstacle for clinical translation is the lack of efficient, robust, and reproducible isolation methods. To bridge that gap, we developed a microfluidic, non-contact, and low-input volume compatible acoustic trapping technology for EV isolation that enabled downstream small RNA sequencing. In the current study, we have further automated the acoustic microfluidics-based EV enrichment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 40 publications
0
22
0
Order By: Relevance
“…Besides successfully enriching EVs, the miRNAs were subsequently extracted 55 . This method of EV isolation was also used later as part of a high-throughput screening to identify miRNA biomarkers for prostate cancer 56 incorporated thermoelectric lysis onto a microfluidic device in order to extract miRNAs directly from cells which was followed by gel electrophoresis to isolate them. When compared to the mirVana isolation kit (Ambion), the chip's performance was miRNA-dependent, performing 110-220 times better for miR-16 and 8.5-14 times better for let-7a (in terms of Ct values obtained).…”
Section: On-chip Extraction With Off-chip Detectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides successfully enriching EVs, the miRNAs were subsequently extracted 55 . This method of EV isolation was also used later as part of a high-throughput screening to identify miRNA biomarkers for prostate cancer 56 incorporated thermoelectric lysis onto a microfluidic device in order to extract miRNAs directly from cells which was followed by gel electrophoresis to isolate them. When compared to the mirVana isolation kit (Ambion), the chip's performance was miRNA-dependent, performing 110-220 times better for miR-16 and 8.5-14 times better for let-7a (in terms of Ct values obtained).…”
Section: On-chip Extraction With Off-chip Detectionmentioning
confidence: 99%
“…55 This method of EV isolation was also used later as part of a high-throughput screening to identify miRNA biomarkers for prostate cancer. 56 Lee et al used electrophoresis to extract miRNAs from serum samples through a nanofilter membrane and demonstrated comparable miRNA Cq values using RT-qPCR to a commercially available miRNA extraction kit, with the whole process of on-chip extraction lasting around 30 min. 57 Behrmann et al incorporated thermoelectric lysis onto a microfluidic device in order to extract miRNAs directly from cells which was followed by gel electrophoresis to isolate them.…”
Section: On-chip Extraction With Off-chip Detectionmentioning
confidence: 99%
“…In this study, NGS was used to identify novel miRNAs in small urinary EVs that could help to distinguish these grades. miRNAs derived from EVs have been used to stratify prostate cancer patients before [ 41 , 42 , 59 ], but previous studies have included patients with ISUP Grades 2 and 3 in the same group. Our results showed that 9 miRNAs had a significantly different expression in at least one of the possible comparisons between those three grades.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, miRNAs from urinary EVs have also been used to discriminate between patients with different GS. When comparing patients with GS 6, 7 and 8, the level of miR-2909 was shown to be higher in more aggressive prostate tumours [ 41 ], and 6 miRNAs have been reported to be differentially expressed in patients with GS ≥ 9 [ 42 ].…”
Section: Introductionmentioning
confidence: 99%
“…Downregulation of miR-27a caused by aberrant AR signalling and PI3K/Akt signalling after ADT was proposed to promote the progression of castration-resistant prostate cancer [352]. Although reports of miR-27a expression in tumour samples are conflicting [352,[354][355][356][357], high serum levels of miR-27a correlate with poor survival [356] and indicate presence of metastases [358].…”
Section: Mirnas Implicated In the Regulation Of Akt And Mycnmentioning
confidence: 99%